Optimal Tourism Development - Juan A. Campos-Soria (MDPI, 2020)
The early days of tourism development had a näive vision of tourism's impacts on society in terms of economic, social, and environmental benefits. Time has passed, and we have learnt lessons regarding the success and failure of tourism development. Mass tourism development has pros and cons and is not necessarily the optimal development model. Alternative development strategies should be contemplated. This Special Issue deals with different topics concerning optimal tourism development. Destination management requires further understanding of different issues, such as carrying capacity, income-based optimal supply size, identification and development of optimal market niches, and adaptation or environmental protection strategies. Tourism planning is concerned with the role of economies of agglomeration, i.e., the advantages of spatial clusters vs scattered development. Additionally, support for and investment in innovation, accessibility, and mobility are relevant nowadays. From the stakeholders' perspective, it is relevant to discuss ways of cooperating and sources of conflicts among different sectors and actors, governance and incentives for sustainable tourism practices, and equity and economic distribution of benefits. Finally, the development of methodological tools for the assessment of optimal tourism development is necessary for policy making, in particular the development of methods that are capable of integrating economic, environmental, and social criteria
Keywords: 650; corporate social responsibility; economic; environmental and social responsibility; Internet; hotel services; Spain; healthy architecture; construction materials; environment; radon; underground building; heritage building; real-estate market; tourist housing; territorial sustainability; sustainable tourism; multicriteria assessment; geographical information systems; sustainable destination; destination image; marketing strategies; communication; segmentation; rural development; National Parks; nature tourism; public use; inbound tourism; China; air pollution; PM2.5; gravity model; spatial statistics; spatial clusters; Moran’ s I; Getis– Ord G (d); LISA; Extremadura; tourist recycling behaviour; environmental barriers; sociodemographic; situational; tourism; spatial analyses; cluster analysis; Ward’ s method; EU; product innovation model; transformative tourism experience; development process design; core resource identification; tourism product development